Lembaga Keuangan Mikro Syariah dan Pemberdayaan UMKM Berbasis Perempuan dalam Upaya Mengurangi Kemiskinan: Studi pada KSPPS Baytul Ikhtiar Bogor - Sofi Maulidia; Mawardi Nur (FOCUS, 2022)
Poverty is a problem that has been rooted in society. One of the efforts to decrease a poverty is empower MSME through Microfinance Institutions because they can directly reach the grass root. This study aims to find out how the pattern and role of women-based MSME empowerment in poverty decrease efforts carried out by KSPPS Baytul Ikhtiar. The research method used is a qualitative method. The results of this study indicate that KSPPS Baytul Ikhtiar adopted a pattern of empowerment of the Grameen Bank which was modified in such a way with sharia principles. In addition, this study also shows that there are 4 main roles of KSPPS Baytul Ikhtiar in poverty alleviation efforts, providing access to capital, providing access to assistance, empowering women and her family.